A Phase II Study of Ziv-Aflibercept in Patients With Advanced Extrapancreatic Neuroendocrine Tumors. Issue 7 (August 2022) - Perez, Kimberly; Kulke, Matthew H.; Horick, Nora K.; Regan, Eileen; Graham, Christopher; Scheutz, Samantha; Stonely, Danielle; Enzinger, Peter C.; Fuchs, Charles S.; Allen, Jill N.; Enzinger, Andrea C.; Clark, Jeffrey W.; et al.
Abstract : Objectives: Neuroendocrine tumors (NETs) are characterized by their expression of vascular endothelial growth factor (VEGF). This trial investigated the activity of Ziv-aflibercept, a recombinant protein that binds to and inhibits the activity of VEGF, in patients with advanced NETs (NCT01782443). Methods: A single-arm, phase II trial enrolling patients with advanced, progressive extrapancreatic NET. Patients were treated with Ziv-aflibercept 4 mg/kg intravenously on day 1 and 15 of a 28-day cycle; the starting dose was reduced to 2 mg/kg on days 1 and 15 of a 28-day cycle because of hypertension-related events. The primary end point was progression-free survival. Results: The trial enrolled 19 patients (13 male:6 female). Patients received a median of 7 cycles (range, 1–18 cycles). The median progression free survival was 11.8 months (95% confidence interval, 3.2–16.1 months), and the median overall survival was 36.4 months (95% confidence interval, 16.1–not reached). Best responses by Response Evaluation Criteria in Solid Tumors 1.1 are as follows: 1 (5%) partial response, 13 (68%) stable disease, 2 (10%) with progressive disease, and 3 (15%) unevaluable. Hypertension occurred in 18 patients (95%), including grade 3–4 hypertension in 12 patients (63%). Conclusions: Although the progression free survival is similar to other VEGF inhibitors in NET, toxicity may preclude further investigation.